Acetylcholinesterase Inhibition and Antioxidant Activities of the Ethanolic Extract of Ya Hom Thip Osot Polyherbal Formula and Its Constituents - Langyanai, Supat; Chaniad, Prapaporn; Kanchanapoom, Kantamaht (KKU Science Journal, 2026)
This study aimed to investigate the acetylcholinesterase (AChE) inhibitory activity and antioxidant properties of the Ya Hom Thip Osot formulation, both in self-prepared samples and those commercially available, as well as ethanol extracts from 46 individual medicinal plants contained in the formula. The results showed that ethanol extracts of both the self-prepared and the commercial Ya Hom exhibited comparable AChE inhibitory activity (37.63 ± 1.93% and 35.87 ± 1.56%, respectively), with no statistically significant difference (p > 0.05). However, their activities were significantly lower than the standard compound Galantamine (94.48 ± 0.26%). Among the individual plant extracts tested, Terminalia chebula Retz. (known in Thai as “Kot Phung Pla”) demonstrated the strongest AChE inhibitory effect (85.99 ± 1.16%). For antioxidant activity evaluated using the DPPH assay, ethanol extracts of the two Ya Hom samples showed EC50 values of 3.55 ± 0.55 and 3.93 ± 1.73 µg/mL, respectively, with no significant difference between them. However, both exhibited significantly lower activity compared to the standard antioxidants L-ascorbic acid and quercetin (p > 0.05). In contrast, Terminalia chebula exhibited remarkably strong antioxidant activity, with an EC50 value of 0.78 ± 0.73 µg/mL, which was significantly more potent than both reference standards. In conclusion, Ya Hom Thip Osot possessed potential AChE inhibitory and antioxidant activities, although its efficacy was lower than standard compounds. Notably, certain individual herbs, particularly Terminalia chebula, demonstrated high activity and showed promise for further development into future health products.